2010
DOI: 10.2514/1.j050111
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an Output-Adaptive, Tetrahedral Cut-Cell Method for Sonic Boom Prediction

Abstract: A cut-cell approach to computational fluid dynamics that uses the median dual of a tetrahedral background grid is described. The discrete adjoint is also calculated for an adaptive method to control error in a specified output. The adaptive method is applied to sonic boom prediction by specifying an integral of offbody pressure signature as the output. These predicted signatures are compared to wind-tunnel measurements to validate the method for sonic boom prediction. Accurate midfield sonic boom pressure sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…9 to 11) and sonic boom predictions (Ref. 12), as well as internal flow applications such as s-ducts (Ref. 13).…”
Section: Flow Solvermentioning
confidence: 99%
“…9 to 11) and sonic boom predictions (Ref. 12), as well as internal flow applications such as s-ducts (Ref. 13).…”
Section: Flow Solvermentioning
confidence: 99%
“…These reconstructed gradients are reduced with a continuously differentiable heuristic limiter that permits good iterative convergence. 42 Backward facing steps, e.g., blunt trailing edges, can create strong expansions in Euler flows. These strong expansions can create difficulties for approximate Riemann solvers.…”
Section: Iiie Fun3d-adjointmentioning
confidence: 99%
“…This motivates the use of anisotropic output-based adaptation; indeed, several studies have shown that the adjoint-weighted residual method coupled with metric-based anisotropic adaptation can reduce the number of solution degrees of freedom an order of magnitude relative to isotropic adaptation. 5,6 While automated a posteriori grid adaptation is attractive for general flows, a priori adaptation can be more efficient if the locations of critical flow features are well known. A common example is refinement of the boundary layer in Reynolds-averaged Navier-Stokes simulations.…”
Section: A Priori Anisotropic Grid Adaptation For Sonic-boom Simmentioning
confidence: 99%